In Vitro Analysis of LPS-Induced miRNA Differences in Bovine Endometrial Cells and Study of Related Pathways - Xinmiao Li; Zhihao Zhang; Xiangnan Wang; Ligang Lu; Zijing Zhang; Geyang Zhang; Jia Min; Qiaoting Shi; Shijie Lyu; Qiuxia Chu; Xingshan Qi; Huimin Li; et al. (Animals)
Lipopolysaccharide (LPS) is one of the main factors inducing endometritis in dairy cows. However, the specific pathogenesis of LPS-induced endometritis in dairy cows is not fully understood. The objective of this study was to establish an in vitro endometritis model using LPS-induced bovine endometrial epithelial (BEND) cells. BEND cells were treated with LPS of different concentrations and times. The cell-counting kit-8 (CCK-8) was used to detect the cell survival rate after LPS treatment, and quantitative real-time PCR (RT-qPCR) was used to detect the expression of control group and LPS-treated group of inflammatory factors interleukin-1 beta (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), and tumor necrosis factor-alpha (TNF-α). The results showed that the survival rate of endometrial epithelial cells stimulated by 5 μg/mL LPS for 6 h was 75.13%, and the expression of inflammatory factors was significantly increased. Therefore, 5 μg/mL LPS for 6 h could be selected as a suitable model for the study of inflammation. In addition, miRNA sequencing and target gene prediction was performed on normal and LPS-treated BEND cells. Among twenty-one differentially expressed miRNAs, six miRNAs were selected and their expression levels were detected by RT-qPCR, which were consistent with the sequencing results. Twenty-one differentially expressed miRNAs collectively predicted 17,050 target genes. This study provides a theoretical basis for further investigation of the pathogenesis of endometritis.